Agroecology matters: impacts of climate change on agriculture and its implications for food security in Ethiopia - Ferede, T.; Ayenew, A.B.; Hanjra, Munir A. (2013)
Climate change poses one of the gravest risks to mankind as it affects a wide variety of socio-economic activities, important to world food security. Agriculture is one of the most important sectors vulnerable to climate change. Agricultural production is sensitive to climate change, and food security is sensitive to agricultural production. Climate abnormalities such as perpetual droughts, floods, heat waves, and rainfall failure can have devastating consequences for agricultural production and the impacts could be immediately transmitted to food security and livelihoods. This chapter attempted to assess the short-run economic impacts of climate change (change in the levels of temperature and precipitation) with a focus on the Ethiopian economy. In doing so, it uses a computable general equilibrium (CGE) model based on the 2005/06 Ethiopian Social Accounting Matrix. One of the innovative approaches of this study is the explicit inclusion of different agro-ecological zones (AEZs) of the country in estimating the likely effects of climate change. The results of the CGE model simulation show that climate change has a dampening effect on economic growth and many key macroeconomic indicators. Investment is the only macroeconomic variable that increases despite the changes in climate. For instance, for a 3.260C increase in temperature and a 12.02mm decline in precipitation which will result in a 9.71% loss in crop production, the CGE model simulation indicated that real GDP declines by 3.83%. Moreover, almost all sectoral activities are affected negatively and different agro-ecologies are affected differently. For instance, the highland part of the country, which is the main producer of food crops, is severely affected compared to other AEZs in terms of agricultural production. The findings further revealed that household livelihoods (measured in terms of real income and welfare) are negatively affected, and the effect is unevenly distributed across different household groups. The highest losses in income and welfare are likely to be incurred by the poor households that are residing in smaller urban centers. Thus, the results of this study call for improved climate adaptation actions at farm level and beyond for reducing both economic decline and welfare loss and enhancing resilience. These results also provide critical information for informing economic policy on climate change and achieving food security.